Condition monitoring of railway vehicles : a study on wheel condition for heavy haul rolling stock - Palo, Mikael (Luleå tekniska universitet, Drift, underhåll och akustik, 2012)
A railway is an energy efficient mode of transport as it uses the low resistance contact between wheel and rail. This contact is not frictionless and causes wear on both surfaces. The wheel-rail guidance is made possible by the shapes of wheel and rail profiles. To increase revenue for train operators and decrease cost for railway infrastructure owners, there is a need to monitor the conditions of the assets. A major cost-driver for operators is the production loss due to wheels, especially from maintenance costs when changing and re-profiling wheels.The research in this study has been performed on the Iron Ore Line (malmbanan) in northern Sweden and Norway. Large parts of this railway line are situated north of the Arctic Circle with temperature variations from -40◦C to +25◦C and a yearly average around freezing. Running trains in this environment strains all components. The purpose of this research is to evaluate how condition-based maintenance should be implemented for railway wagons. Research methods include a literature review, interviews, and data collection and analysis. Manual wheel profile measurements have been combined with maintenance data, weather data and wheel-rail force measurements to make comparisons between seasons and wagons.The analysis shows that there are different lateral force signatures at the wheel-rail interface dependent on the wheel’s position within the bogie. It also shows the need to change both wheel sets of the bogie simultaneously. Finally, it proves there is greater wheel wear at low temperatures.